2007
DOI: 10.1029/2006gl029156
|View full text |Cite
|
Sign up to set email alerts
|

Salinity‐induced hydrate dissociation: A mechanism for recent CH4 release on Mars

Abstract: [1] Recent observations of CH 4 in the Martian atmosphere suggest that CH 4 has been added relatively recently. Several mechanisms for recent CH 4 release have been proposed including subsurface biological methanogenesis, abiogenic hydrothermal and/or volcanic activity, dissociation of CH 4 hydrates, atmospheric photolysis, or addition of organics via bolide impact. This study examines the effects of increasing salinity on gas hydrate stability and compares estimates of the Martian geothermal gradient to CH 4 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(7 citation statements)
references
References 47 publications
0
7
0
Order By: Relevance
“…This is potentially important to subpermafrost geochemistry, as CH 4 hydrate formation and dissipation can affect gas chemical composition and fluid chemical and isotopic composition (Trofimuk et al 1974; Hesse and Harrison 1981; Milkov et al 2004). The subsurface temperature and pressure conditions at the U‐tube sample depth were within the CH 4 hydrate stability field, given the salinity of the matrix fluid (Elwood Madden et al 2007). Owing to the lack of gas quantity data, it was not possible to confirm the presence of CH 4 hydrates.…”
Section: Discussionmentioning
confidence: 99%
“…This is potentially important to subpermafrost geochemistry, as CH 4 hydrate formation and dissipation can affect gas chemical composition and fluid chemical and isotopic composition (Trofimuk et al 1974; Hesse and Harrison 1981; Milkov et al 2004). The subsurface temperature and pressure conditions at the U‐tube sample depth were within the CH 4 hydrate stability field, given the salinity of the matrix fluid (Elwood Madden et al 2007). Owing to the lack of gas quantity data, it was not possible to confirm the presence of CH 4 hydrates.…”
Section: Discussionmentioning
confidence: 99%
“…However, clathrates are also known to be unstable in the presence of salts since both species compete for water (e.g., Elwood Madden et al. ; Safi et al. ).…”
Section: Freezing Of the Oceanmentioning
confidence: 99%
“…In fact, in some of the areas from where methane emissions appear to have originated, retreating glaciers have been detected (Head et al 2005). A related version of this idea is that the hydrate dissociation and CH 4 release is triggered by small changes in salinity (Elwood Madden et al 2007). The Planetary Fourier Spectrometer experiment on board Mars Express has shown that methane correlates well with the water vapour in the atmosphere and with the near-surface ice-enriched areas at middle and low latitudes identified by Mars Odyssey (Formisano 2005).…”
Section: Methane In the Martian Atmospherementioning
confidence: 99%